2007
DOI: 10.1016/j.juro.2007.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Acupressure as a Treatment for Anxiety Before Extracorporeal Shock Wave Lithotripsy in the Elderly

Abstract: Elderly patients who received auricular acupressure at specific relaxation points while being transported to the hospital were less anxious, anticipated less pain and were more optimistic about the outcome of treatment that they will receive than the sham treated group. These data prove that this is an effective treatment for anxiety that improves the patient overall perception of ESWL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 19 publications
1
35
0
1
Order By: Relevance
“…Even though previous studies have been conducted in a different setting and on a different patient population, the same positive results can suggest that acupressure is effective in reducing anxiety. Similarly, acupressure was also found to reduce surgery-related anxiety in women with post-cesarean section (Chen et al, 2005) and in elderly patients before receiving extracorporeal shock wave lithotripsy (Mora et al, 2007). However, two studies conducted among pre-operative patients showed unclear findings that acupressure and sham acupressure equally reduced anxiety (Agarwal et al, 2005;Valiee et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Even though previous studies have been conducted in a different setting and on a different patient population, the same positive results can suggest that acupressure is effective in reducing anxiety. Similarly, acupressure was also found to reduce surgery-related anxiety in women with post-cesarean section (Chen et al, 2005) and in elderly patients before receiving extracorporeal shock wave lithotripsy (Mora et al, 2007). However, two studies conducted among pre-operative patients showed unclear findings that acupressure and sham acupressure equally reduced anxiety (Agarwal et al, 2005;Valiee et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…In 2007, another study was conducted with preoperative auriculopressure in 100 elderly patients, prior to lithotripsy, using the same protocol used for patients in the hospital. Positive results were found with the relaxation point when compared to the placebo point selected (17). Therefore, in these studies, the extent of relaxation by auriculotherapy was functional, independent of the therapist and his training.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, in some studies (16,17) of auriculotherapy on preoperative anxiety, the interventionists were not necessarily acupuncturists, and technique was effective, simple, non-invasive and could be used by different professionals and also by paramedics transporting patients by ambulance to the hospital from their homes (16) . One of the studies utilized auriculopressure to reduce anxiety in patients with gastrointestinal complaints, during transport by ambulance, in which they chose only two points, for group for relaxation and one group for placebo.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, acupuncture has been described to aid in the management of chronic prostatitis, chronic pelvic pain as well as nocturnal enuresis (29,(36)(37)(38). In stone disease field, acupuncture has been used for treating renal colic (28) and for extracorporeal shock wave lithotripsy (SWL) -related pain and anxiety (30,37,(39)(40)(41)(42).…”
Section: Historical Considerationsmentioning
confidence: 99%
“…Therefore, acupressure proved to be a useful measure for decreasing anxiety in the pre-interventional urological setting. The authors proposed that minimal equipment and training is required, making it a technique applicable to any physician, nurse, paramedic or medical technician (40).…”
Section: Supporting Objective Evidencementioning
confidence: 99%